PENGELOLAAN PEMBELAJARAN CAMPURAN (BLENDED LEARNING) PADA PROGRAM PENDIDIKAN KECAKAPAN WIRAUSAHA DI LKP NUNING KOTA CIMAHI - Nadyatiana Sagita, - (2021)
This research is motivated by the presence of blended learning which is an alternative solution for organizing learning during a pandemic in non-formal units at the Course and Training Institute. The objectives of this study were to obtain data: 1) management of blended learning, 2) Supporting and inhibiting factors of blended learning, 3) Readiness of course participants during learning during a pandemic. This research uses a qualitative approach with a case study method. Techniques in data collection using observation, interviews and documentation studies. The subjects in the study amounted to two instructors, one manager and three course participants from the Nuning Training Course Institute (LKP). The results obtained are that the management of blended learning is through the planning stage, namely the analysis of the characteristics of the course participants, as well as the preparation of learning programs consisting of needs analysis, determination of learning outcomes, content analysis, development and selection of learning objects and activities, and evaluation of learning. The implementation stages are in accordance with the four blended learning learning settings, namely 1) Live synchronous, 2) Self-paced learning, 3) Collaboration, 4) Assessment, 5) Performance support and materials. The evaluation stage using Kirkpatrick analysis obtained information that the reaction stage was carried out based on observation without the existence of an assessment in the form of a questionnaire of student satisfaction with learning. The existence of support between the seven components of the training system is a determinant of the success of implementing blended learning at LKP Nuning. In addition, the ability of course participants to use technological devices, as well as the support capacity of human resources at course institutions in creating various learning innovations with the role of technology, make blended learning able to be carried out sustainably in course and training institutions. Keywords: blended learning; management; training; readiness; perception